ISU FEMINISME DALAM NOVEL PUTRI KARYA PUTU WIJAYA - NFN Arriyanti (Madah: Jurnal Bahasa dan Sastra, 2014)
This paper discusses about issues of feminism in a novel titled Putri written by Putu Wijaya. The discussing about women issues will be analyzed by applying feminism ways of thinking. Issues of feminism will be seen by looking at the main character of the novel. Feminism issues in the novel appear because of the behavior and attitude of the heroine in struggling her will. The rejection toward different gender stereotypes which tends to cut women rights as human being and member of society is the reflection of the heroine‘s attitude.Tulisan ini mengkaji isu feminisme yang terkandung di dalam novel Putri karya Putu Wijaya. Pembahasan wacana perempuan ini dikupas dengan memanfaatkan kajian feminis. Isu feminisme ini diamati dari tokoh utama cerita, yaitu Putri. Isu feminisme dalam novel Putri muncul karena adanya sikap dan perilaku tokoh utama perempuan dalam mewujudkan dan memperjuangkan keinginannya. Penolakan terhadap perbedaan stereotip gender yang cenderung mengebiri hak-hak perempuan sebagai manusia dan anggota masyarakat merupakan wujud perilaku tersebut.